Lead-free zero dimensional tellurium(iv) chloride-organic hybrid with strong room temperature emission as a luminescent material - Biswas, Anupam; Bakthavatsalam, Rangarajan; Bahadur, Vir; Biswas, Chinmoy; Mali, Bhupendra P.; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Despite the current progress in `Pb-free' low dimensional main group metal halide based luminescent materials, it is challenging to synthesize Te(iv) halide hybrids with strong ambient emission with excitation features in the visible range as efficient and stable phosphors for potential lighting applications. Reported here is a (benzyltriethylammonium)(2)TeCl6 zero dimensional hybrid material with excitation features in the visible range and strong room temperature, broadband, intrinsic luminescence (PLQY similar to 15%) arising due to self-trapped excitons (STEs). Furthermore, a proof-of-concept LED architecture demonstrates successful optical down-conversion with a visible light excitation source. Here, exclusive adoption of a `regular' octahedral Te(iv)-halide unit structure with minimal static distortion provides a unique opportunity to unmask the role played by 5s(2) lone pair electrons in shaping the emissive properties. This effort may open up new avenues towards unravelling the role of lone pair stereoactivity in controlling the PLQY in low dimensional hybrids that has proven to be challenging for the reported (Sb, Sn) based low dimensional 5s(2) metal halide hybrid materials.